THE PROBLEMS IN TEACHING AND LEARNING SPEAKING ENGLISH FOR INDONESIAN LABORS - Ummah, Siti Sumihatul (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
Speaking English is one of English skills that must be mastered by Indonesian labors. By having good speaking English, they can communicate to the foreigners at aboard. This research was conducted at PT. Assanatama Karya Mandiri Surabaya. The research purposes were to investigate the problems in teaching speaking English for Indonesian labors faced by an instructor, to investigate the problems in learning speaking English faced by Indonesian labors, to know the instructor’s ways in solving the teaching speaking English problems, and to know the Indonesian labors’ ways in solving the learning speaking English problems. The research method was qualitative descriptive. The data sources were from the instructor and Indonesian labors. There were two ways to collect the data namely interview and documentation. The result of research showed that there were four problems that usually faced by the instructor in teaching speaking English for Indonesian labors namely the difficulty in practicing speaking English, difficulty in managing time allotment, lack of dicipline, and the use of correct English pronuonciation. The problems in learning speaking English faced by Indonesian labors were the difficulty in memorizing English vocabularies, inhibition, mispronounciation, lack of self-confidence or shyness, and lack of interest and motivation. Here, there were some ways done by the instructor to solve these problems such as creating joyful learning strategy, adding class program, giving reward and pedagogy punishment, and giving drilling by using audio visual media. Furthermore, the solving problems in learning speaking English done by Indonesian labors were memorizing the English vocabularies by using familiar songs, practicing speaking English by using dialog scripts at Dormitory, joining English pronounciaton program at the language laboratory, guidancing speaking English with classmate, and sharing the lesson with classmate.